2009
DOI: 10.1103/physrevb.80.235308
|View full text |Cite
|
Sign up to set email alerts
|

Surface and interstitial transition barriers in rutile (110) surface growth

Abstract: We present calculated surface and interstitial transition barriers for Ti, O, O-2, TiO, and TiO2 atoms and clusters at the rutile (110) surface. Defect structures involving these small clusters, including adcluster and interstitial binding sites, were calculated by energy minimization using density-functional theory (DFT). Transition energies between these defect sites were calculated using the NEB method. Additionally, a modified SMB-Q charge equilibration empirical potential and a fixed-charge empirical pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 26 publications
1
17
0
Order By: Relevance
“…14 Ti interstitials and adatoms are therefore of paramount importance to the surface structures, 15 the surface chemistry 16 and the growth of titania, and it is desirable to have modelling schemes that can describe these species, their reactivity and their mobility. 17 Modelling schemes that accurately represent electronic and geometric structures are particularly challenging for non-stoichiometric materials with variable oxidation states. The description of reduced rutile has been an active topic for many years, with much discussion as to whether the dominant species involved are Ti interstitials 15 or oxygen vacancies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Ti interstitials and adatoms are therefore of paramount importance to the surface structures, 15 the surface chemistry 16 and the growth of titania, and it is desirable to have modelling schemes that can describe these species, their reactivity and their mobility. 17 Modelling schemes that accurately represent electronic and geometric structures are particularly challenging for non-stoichiometric materials with variable oxidation states. The description of reduced rutile has been an active topic for many years, with much discussion as to whether the dominant species involved are Ti interstitials 15 or oxygen vacancies.…”
Section: Introductionmentioning
confidence: 99%
“…17 provides a thorough exploration of the diffusion of Ti and O ad-species on the rutile (110) surface using density functional theory (DFT) with the local density approximation (LDA). However, it is known that this approach will not describe well the localisation of d-electrons that are expected in reduced titania.…”
Section: Introductionmentioning
confidence: 99%
“…19 Periodic boundary conditions were used for the substrate, mimicking the bulk, and the Coulomb interaction between atoms was calculated using Ewald summation. Typical system sizes were five layers with ;200 atoms in each layer.…”
Section: Methodsmentioning
confidence: 99%
“…4,7,11 Numerous groups have modeled deposition processes of thin films, 12-14 but here we look specifically at TiO 2 . [15][16][17][18][19][20] Previous work carried out on the stoichiometry of deposition shows that reactive sputtering growth using an oxygen-rich plasma produces the most crystalline films; 16,17 however, it was found that when only pure oxygen interacts with the surface, etching occurs after the initial oxidation. 18 In this article, we investigate, at the atomistic level, the effect of these different deposition processes on the a) layer-by-layer growth of rutile TiO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…[37][38][39] This is an example where there is direct microscopic evidence of the oxidation and growth of this surface. 40 The experiments were able to show that during oxidation, O 2 molecules were mobile on the rutile (110) surface.…”
Section: Film Growth Dependent On Complex Reaction Pathwaysmentioning
confidence: 99%